Exploring the Landscape of work readiness in vocational students: A Bibliometric Analysis - Baandaalr Lizein; Hari Mulyadi; Endang Supardi; Fadli Agus Triansyah (Kontigensi : Jurnal Ilmiah Manajemen, 2024)
The aim of this research is to determine the trend of publications related to internships in student work readiness in the last three years after the Covid-19 pandemic. The database used is Scopus. The method used is bibliometric descriptive analysis. The research stages included identification, screening, eligibility assessment, and inclusion, resulting in 152 publications as final data. The research results show that the number of publications related to work readiness has increased in the last few years after the pandemic. Australia has a significant influence on research in this area compared to other countries. In the context of the COVID-19 pandemic which is also present in the data ("covid-19" and "pandemic"), it is important to understand how work readiness can change and adapt to changes in the world of work caused by crisis situations like this. In the educational context, “curriculum” and “higher education” are also relevant because they play an important role in preparing individuals for future employment. The importance of "leadership" and "learning" cannot be ignored in increasing work readiness, because leadership skills and the ability to continue learning are important aspects in achieving high work readiness. New themes that emerged in this research include leadership, transition, higher education, baccalaureate and pandemic. Thus, the topic of “work readiness” is not only important in the research context, but also has strong significance in understanding how individuals can be successful in the world of work and how education and training can be adapted to achieve this goal.